Penguatan Keadilan Organisasi Dan Kepuasan Kerja Dalam Upaya Peningkatan Organizational Citizenship Behaviour Guru SMK - Prihandini, Agustina Isworo; Wulandari, Dian; Retnowati, Rita (JURNAL MANAJEMEN PENDIDIKAN, 2023)
STRENGTHENING ORGANIZATIONAL JUSTICE AND JOB SATISFACTION IN AN EFFORT TO IMPROVE ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB)The purpose of this study is to empirically determine the Strengthening of Organizational Justice and Job Satisfaction in an Effort to Increase Organizational Citizenship Behavior (OCB) of Private Vocational School Teachers in Citeureup District, Bogor Regency. The total research sample was 166 teachers who were randomly drawn using proportional random sampling techniques from 283 teachers from the population. The correlational descriptive method was used in this study using a quantitative approach. This study resulted in three conclusions: 1) The positive and significant relationship between Organizational Justice (X1) and Organizational Citizenship Behaviour (Y) is shown by a correlation coefficient of ry1 of 0.56 and Organizational Justice contributes 31% to the teacher's Organizational Citizenship Behaviour. 2) The positive and significant relationship between Job Satisfaction (X2) and Organizational Citizenship Behaviour (Y) is shown by a ry2 correlation coefficient of 0.812 and Job Satisfaction contributes 66% to the teacher's Organizational Citizenship Behaviour. 3) There is a positive relationship between Organizational Justice (X1) and Job Satisfaction (X2) together with Organizational Citizenship Behaviour (Y) which is shown by a correlation coefficient of 0.82 which together contributes 68% to Organizational Citizenship Behaviour. Based on these findings, teacher OCB can be improved through organizational Justice and job satisfaction. From SITOREM's analysis of the 16 indicators studied, the results were obtained that there were 4 indicators that were maintained/developed, namely salary indicators, opportunities for self-development, superior attitudes, and performance appraisals. While there are 12 indicators that are priorities to improve.